Multi-seasonal water-stress memory versus temperature-driven dynamic structural changes in grapevine. (8th January 2021) - Shtein, Ilana; Wolberg, Shunamit; Munitz, Sarel; Zait, Yotam; Rosenzweig, Tovit; Grünzweig, José M; Ohana-Levi, Noa; Netzer, Yishai
Abstract: Perennial plants perpetually adapt to environmental changes in complex and yet insufficiently understood manner. We aimed to separate the intra-seasonal temperature effects on structure and function from perennial and annual water stress effects. This study focused on grapevine ( Vitis vinifera L. 'Cabernet Sauvignon') petioles, which being a continuously produced organ, represent the current status of the plant. Field-grown mature plants subjected to multi-annual irrigation treatments (severe water stress, mild water stress and non-stressed) throughout the growing season were compared with greenhouse-grown plants under three temperature regimes (22, 28 and 34 °C). Physiological and functional anatomy parameters were measured. A generalized additive model (GAM) based on meteorological and lysimeter-based field data was applied to determine the relative influence of various meteorological parameters on evapotranspiration (ETc ) during the growing season in the field experiment. At the beginning of the growing season, in May, petioles in the severe stress treatment showed a stress-related structure (decreased length, safer hydraulic structure and increased lignification), though having high values of stem water potential (SWP). As the season progressed and temperatures increased, all water availability treatments petioles showed similar changes, and at the end of season, in August, were structurally very similar. Those changes were independent of SWP and were comparable to high temperature-induced changes in the greenhouse. In contrast, stems hydraulic structure was strongly influenced by water availability. Regression analyses indicated a relationship between petioles xylem structure and stomatal conductance ( g s ), whereas g s (but not SWP) was temperature-dependent. The GAM showed that ETc was mainly dependent on temperature. Our results indicate a perennial water-stress memory response, influencing the petiole structure at the beginning of the following season. Intra-seasonally, the petiole's structure becomes independent of water status, whereas temperature drives the structural changes. Thus, ongoing climate change might disrupt plant performance by purely temperature-induced effects.